Assessment of Quality of Life in Hypertensive Patients - Sattanathan Kaliyaperumal, Sagarika Binitha Hari, Prasanth Kumar Siddela, Sara Yadala (Journal of Applied Pharmaceutical Science, 2016)
Assessing the quality of life of hypertensive patients is an important issue as it’s much worse than healthy individuals. The aim of the study was to assess the quality of life in the hypertensive patients and to evaluate the functional capacity, physical aspects, pain, general health, vitality, social aspects, emotional aspects and mental health of the patient. The Study was conducted in a Tertiary care Hospital, Erode. A total of 300 patients were selected in the study period of 6 months. Short form 36 item (SF-36) health survey questionnaire was used in this study to assess the quality of life in hypertensive patients. In the present study, mental health (Avg. score 25.8) was the component mostly affected in hypertensive patients followed by emotional aspects (Avg. score 33.43) and vitality (Avg. score 36). Social aspects (Avg. score 83.14), physical aspects (Avg. score 75.4) and functional capacities (Avg. score 67.1) appear to be least affected. Pain (Avg. score 49.3) was moderately affected and physical aspect (Avg. score 75.4) was least affected by hypertension. Proper treatment and awareness about hypertension is necessary for the patient’s mental and emotional well being.
Keywords: Hypertension, quality of life, mental health, patient awareness.